Mediation - the Malaysian Dental Association experience - Purmal, K.; Nambiar, P. (Wiley, 2009)
Objectives: To study the success and failures of the mediation process of complaints from 2004-2007 by the Complaints Bureau Steering Committee and the Public Complaints Bureau Committee of the Malaysian Dental Association (MDA). Methods: Retrospective analysis of complaints from the records at the MDA. Results: There were 41 cases during the three years, most involved surgical procedures (9), endodontics (9), miscellaneous (8), orthodontics (6), restorative problems (6) and prosthetics (2). Chinese patients made the most complaints (67) followed by Malay patients (23), foreigners (7) and Indians (3). 69 of the cases where against dentists working in the KIang Valley, 14 in Johore and the rest in various part of the country. 69 of the cases were successfully mediated, 10 unresolved and the 21 are in various stages of mediation. Conclusion: It is heartening to report that the MDA has successfully mediated in a sizeable number of the complaints which are increasing yearly.